Statistics for anthropology - Madrigal, Lorena (Cambridge : Cambridge University Press, 2012)
"Anthropology as a discipline is rapidly becoming more quantitative, and anthropology students are now required to develop sophisticated statistical skills. This book provides students of anthropology with a clear, step-by-step guide to univariate statistical methods, demystifying the aspects that are often seen as difficult or impenetrable. Explaining the central role of statistical methods in anthropology, and using only anthropological examples, the book provides a solid footing in statistical techniques. Beginning with basic descriptive statistics, this new edition also covers more advanced methods such as analyses of frequencies and variance, and simple and multiple regression analysis with dummy and continuous variables. It addresses commonly encountered problems such as small samples and non-normality. Each statistical technique is accompanied by clearly worked examples, and the chapters end with practice problem sets"--
Machine generated contents note: Preface; List of partial statistical tables; 1. Introduction to statistics and simple descriptive statistics; 2. The first step in data analysis: summarizing and displaying data. Computing descriptive statistics; 3. Probability and statistics; 4. Hypothesis testing and estimation; 5. The difference between two means; 6. The analysis of variance (ANOVA); 7. Non-parametric tests for the comparison of samples; 8. The analysis of frequencies; 9. Correlation analysis; 10. Simple linear regression; 11. Advanced topics in regression analysis; References; Index.
Includes bibliographical references and index.
Keywords: Anthropology -- Statistical methods